Desenvolvimento de procedimentos de análise por injeção em fluxo para a determinação de furosemida, paracetamol e acetilcisteína em formulações farmacêuticas - Vieira, Heberth Juliano (2006)
In this thesis are presented the development of flow injection analysis procedures with spectrophotometric detection for determination of furosemide, paracetamol and acetylcysteine in samples of pharmaceutical formulations. A flow injection system was optimized for indirect determination of furosemide monitoring the excess of sodium hypochlorite not consumed in the reaction with the furosemide using o-tolidine as reagent at 430 nm. The analytical curve was linear from 5.0x10-6 to 8.0x10-5 mol L-1 and the detection limit was 2.5x10-6 mol L-1. A RSD smaller than 2.0% (n=10) for 1.0x10-5 and 5.0x10-5 mol L-1 furosemide solutions and an analytical frequency of 60 determinations h-1 were obtained. Another flow injection system was proposed to determine paracetamol in pharmaceutical samples employing sodium hypochlorite and o-tolidine as reagents. In this flow system, sodium hypochlorite reacted with paracetamol and its concentration in excess was monitored with o-tolidine. After system optimization, the analytical curve was linear in the paracetamol concentration range from 8.5x10-6 mol L-1 to 2.5x10-4 mol L-1 with a detection limit of 5.0x10-5 mol L-1. A RSD of 1.2% (n=10) was obtained for 1.5x10-4 mol L-1paracetamol solution. The analytical frequency of the system was 60 determinations h-1. The otolidine and its products used in both proposed flow injection systems were on line destroyed using an ultraviolet lamp (λ=380 nm) and hydrogen peroxide solution. The reversed flow system was proposed for determination of paracetamol employing sodium nitrite as reagent. The product formed was monitored at 400 nm. The analytical curve was linear in the paracetamol concentration range from 4.0x10-5 to 1.1x10-3 mol L-1 with a limit of detection of 2.0x10-5 mol L-1 and analytical frequency of 45 determinations h-1. RSD smaller than 2% were obtained for 8.0x10-4 and 1.0x10-3 paracetamol solutions. A flow system injection procedure with spectrophotometric detection to determine acetylcysteine was developed. In this procedure, acetylcysteine reacts with Ce(IV) solution and the excess of cerium (IV) was monitored with ferroin at 500 nm. An analytical curve ranged from 1.32x10-5 to 1.35x10-4 mol L-1 with a limit of detection of 8.0x10-6 mol L-1 were obtained. A RSD of 1.4% (n=10) for 2.2x10-5 mol L-1 acetylcysteine solution and an analytical frequency of 60 determinations h-1 were obtained. Another flow injection system for determine acetylcysteine using bromine (Br2) as reagent was also proposed. In this system, Br2 chemically generated on line reacts with the analyte and its excess monitored at 400 nm. The analytical curve obtained was linear from 1.6x10-4 and 1.6x10-3 mol L-1 and RSD of 1.2 % (n=10) for 5.3x10-4 solution were obtained. The system showed the analytical frequency of 60 determinations h-1 and ascorbic acid solution was used to destruct bromine on line.